2011
DOI: 10.3109/00365521.2011.610005
|View full text |Cite
|
Sign up to set email alerts
|

Is smoking a risk factor for collagenous colitis?

Abstract: Objective. The association between smoking and idiopathic inflammatory bowel disease is well known; smoking seems to have a diverse effect. Crohn´s disease is associated with smoking, while ulcerative colitis is associated with non-smoking. Data on smoking in microscopic colitis of the collagenous type (CC) is lacking. The aim of this investigation was to study smoking habits in collagenous colitis and to observe whether smoking had any impact on the course of the disease. Materials and Methods.116 patients (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
5
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 28 publications
1
51
5
2
Order By: Relevance
“…A majority of the nine patients (seven of nine) were also smokers (Table I). This is in line with previous observations indicating that both CC and LC patients tend to be smokers [31,32].…”
Section: Discussionsupporting
confidence: 82%
“…A majority of the nine patients (seven of nine) were also smokers (Table I). This is in line with previous observations indicating that both CC and LC patients tend to be smokers [31,32].…”
Section: Discussionsupporting
confidence: 82%
“…Помимо сопутствующих аутоиммунных заболеваний клини-чески значимым ФР развития МК является курение [24]. Недав-но завершенное крупное проспективное исследование случай-контроль F. Fernández-Bañares и соавт.…”
Section: терапевтический архив 4 2015unclassified
“…Thus, in a study by Vigren et al [45], it was found that 37% of CC patients smoked compared to 17% in the control group, whereas in the age group 16-54 years, this was as high as 50% compared to 18% in the control group. Furthermore, in this study active smokers were diagnosed with CC 10 years earlier compared to nonsmokers, results that were corroborated by Fernandez-Banares et al [46].…”
Section: Etiology and Pathogenesismentioning
confidence: 99%